Exploring the emotional intelligence of Florence Nightingale - Edna Ruiz Magpantay-Monroe (Elsevier, 2015)
Objective: Emotional intelligence (EI) within nursing appears to be a growing interest as evidenced by the expanding number of literature reviews conducted on the subject. The inquiry for this historical research is to understand the work and characteristics of Florence Nightingale and EI. Methods: The assumption is that nurses who are emotionally intelligent are the most likely to not only survive the nursing profession but to thrive and make compassionate future leaders. Nightingale's letters, pictures and other writings were used to evaluate her viewpoints as an inspirational nurse and leader. Results: Nightingale was a catalyst for change; internally motivated to be a great nurse and had the zeal to develop others as well. Conclusions: Exploring Nightingale's characteristics of EI such her confidence, determination, integrity and compassion, her teachings and beliefs can transcend time to mold successful nurses more than a century later. "The voice of a leader. It is as resounding as the heart it encourages, as far-reaching as the change it invokes. It is tuned by its keen sense of the voices around it and speaks back in a language they can understand. Its breath enters all that truly hear it, and when it no longer speaks, it can still be heard." Mae Taylor Moss